Permasalahan dan Solusi Pengembangan Perbankan Syariah di Kota Madiun - Ana Dhaoud Daroin, Aprilia Putri Ningtias (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
Islamic banks implement a new concept that is not the same as the concept that has been known and embraced by conventional banking. The rapid development of banking today is not matched by an increase in the quality of its services. Many banks are only concerned with services in certain aspects by ignoring other aspects of service. The objectives in this study are (1) to identify the problems faced; (2) identify development efforts made by Islamic banks in Madiun. This research is a qualitative research with a phenomenological approach, by the descriptive method. Data processing techniques and checking the validity of the data is done by data triangulation techniques. Triangulation of data used in this study is the triangulation of methods and triangulation of theory. The results of the research findings state that the problems faced by Islamic banks in the city of Madiun in terms of HR and products. Problems in terms of HR include work motivation of employees, the level of public trust in Islamic banks is still low and the wrong mindset about Islamic banking. The problem in terms of products is the existence of miss perception of the contract between the customer and the bank. Development solutions carried out by banks through employee trainees and certification programs then conduct certification evaluations. In terms of products promoting the #ayohijrah program, and cooperating with basic Islam. In terms of services, there is a prizes savings program and ball pick-up strategy